2019
DOI: 10.1101/696344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dose-Dependent Effects of Transcranial Alternating Current Stimulation on Spike Timing in Awake Nonhuman Primates

Abstract: Weak extracellular electric fields can influence spike timing in neural networks. Approaches to impose such fields on the brain in a noninvasive manner have high potential for novel treatments of neurological and psychiatric disorders. One of these methods, transcranial alternating current stimulation (TACS), is hypothesized to affect spike timing and cause neural entrainment. However, the conditions under which these effects occur in-vivo are unknown. Here, we show that TACS modulates spike timing in awake no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 60 publications
11
30
0
Order By: Relevance
“…The current results show that phonological processing improved via a focal and specific enhancement of 30-Hz oscillatory activity in left auditory cortex. This finding confirm others showing that tACS can indeed influence neuronal activity in a frequency-and location-specific manner [43,44]. Phonological performance improvement hence likely reflects changes in neuronal entrainment towards the frequency of the tACS stimulation [43,45].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current results show that phonological processing improved via a focal and specific enhancement of 30-Hz oscillatory activity in left auditory cortex. This finding confirm others showing that tACS can indeed influence neuronal activity in a frequency-and location-specific manner [43,44]. Phonological performance improvement hence likely reflects changes in neuronal entrainment towards the frequency of the tACS stimulation [43,45].…”
Section: Discussionsupporting
confidence: 89%
“…If stabilized by repeated stimulation, this large-scale effect might also confer the 30 Hz tACS procedure the interesting advantage of (re)circumscribing phonemic processing to the left hemisphere, an important functional property for improving reading speed in the longer run. Future protocols might also exploit dose-dependent neural entrainment by tACS to tailor stimulation intensity to individual neural deficit in gamma activity [44].…”
Section: Discussionmentioning
confidence: 99%
“…3A). Oscillating electric fields at 0.3 V m À1 or higher can induce immediate electrophysiological effects, e.g., modulate spike timing activity of single neurons [39,41]. None of our participants reported experiencing phosphenes during stimulation, but they did report a mild to moderate degree of transient skin sensations, which did not differ across the stimulation conditions (nonparametric ANOVA p ¼ 0.99, more details in Methods).…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, the model-driven tACS results showed that the electrical stimulation of the right but not the left posterior brain region during encoding improved subsequent recognition by particularly enhancing the familiarity process. Mechanistically, we suppose that the alternating current facilitated the synchronization in the parietal neuronal population [39,41] and dependent neural communications [16,59]. The increased degree of neural synchrony likely improved feature binding during encoding and made the stimulus more familiar at the next encounter.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation